Menyoal Peroblematika Pembelajaran Pendidikan Agama Islam Di SMK Negeri 3 Sorong - Fardan Abdillah M; Hermanto Hermanto (Al-Riwayah : Jurnal Kependidikan, 2020)
This paper examines the problems of learning Islamic education subject at SMK Negeri 3 Sorong. Islamic education is one of the compulsory subjects in schools at every level of education, from elementary until high school and university. At SMK Negeri 3 Sorong, Islamic education subject is a normative subject that is give a students chance to become good believers, fear to Allah SWT, are become a good person, and have a complete personality. With Islamic education subject in the schools, student are expected to understand, appreciate and practice the teachings of Islam in everyday life. Although Islamic education has been teached at SMK Negeri 3 Sorong, ethical and moral deviations students still a big problem. Drinking alcohol, promiscuity, often skipping school, lying, talking harshly, and fighting still perform by the student. This paper interested in researching the problems of Islamic education subject at SMK Negeri 3 Sorong. The results of this study are: First, learning Islamic education subject at SMK Negeri 3 Sorong faces various problems. Most students have not been capability to read the Alquran, lack of cooperation between teachers and students, the teachers have not applying personal and professional competences in learning, limited time to learn a subject, school facilities and infrastructure that have not optimally supported in Islamic learning subject. Second, SMK Negeri 3 Sorong has made various efforts in addressing the problems of Islamic education subject. Especially, the program of reading the Qur'an once a week, praying dzuhur jamaah at the mosque, and religious extracurricular activities such as monthly recitation for teachers and students